Antimicrobial and anti-biofilm activity of titanium dioxide nanoparticles alone and in combination with erythromycin against methicillin-resistant Staphylococcus aureus - Issam Jumaa Naser (Journal of Pure & Applied Sciences, 2022)
Background: S. aureus is a major pathogen and the predominant bacteria that causes hospital-acquired infections. TiO2NPs have unique characteristics and expanding use for different applications in nanomedicine and have attracted enormous interest in the various rising nanoproducts. Objective: To evaluate the anti-bacterial and anti-biofilm activities of TiO2NPs alone and in combination with the macrolide class of drugs (Erythromycin) against S. aureus isolated from different clinical specimens. Methods: Kirby-Bauer’s disk diffusion technique was applied for antimicrobial susceptibility testing against S. aureus isolates. The Minimum inhibitory concentrations of TiO2NPs and erythromycin were performed with the broth microdilution method, while biofilm formation was investigated by the Calgary technique. Results: At a total of eighty-five strains of S. aureus clinical isolates from patients who are in hospitals in the medical city of Baghdad, 34 (40%) of S. aureus were sensitive to penicillin class (Methicillin) while 51 (60%) were resistant to methicillin, with statistical significance between both groups (P